Environmental friendly carrier material for nifedipine as hypertension drug - E. Budianto; S.H. Astuti (Global Journal of Environmental Science and Management)
Nifedipine is a hypertension drug must be consumed three times a day due to its low oral bioavailability. One way of developing a controlled drug delivery system is making nifedipine microcapsules by using environmentally friendly polymers of polylactic acid and polycaprolactone via the evaporation method using oil-in-water solvents. Polylactic acid and polycaprolactone can be said to be environmentally friendly polymers, because they can be degraded naturally in nature both in the biotic, and abiotic environment, or microorganism. In this study, polylactic acid, Polycaprolactone, and nifedipine were dissolved in dichloromethane solvent; then, an emulsifier was added for the emulsification stage. After passing through the dispersion stage for the process of compaction of the microcapsules by solvent evaporation, the microcapsules were filtered. Microcapsules were characterized using particle size analysis, X-ray diffractometry, and scanning electron microscopy, respectively. The drug release percentage was determined by dissolving microcapsules for 55 hours using a buffer at the potential of hydrogen 1.2 and pH 7.4 as dissolution media. In this study, all variations in the composition of polyblend resulted in a percent efficiency of encapsulation ranging from 78.82%-89.84%, and percent release ranging from 6.80%-39.07%. The composition of 100% polylactic acid produces the highest percent encapsulation efficiency of 89.84% but produces the lowest percentage of drug release at 6.80%. The best composition obtained was polylactic acid: polycaprolactone 1:9 (weight per weight), with a percent release of 39.07% and percent encapsulation of 78.82%. Microcapsule solids produced are approximately 96%. Particle Size of microcapsule ranges at 0.5 μM.